Adverse Cutaneous Drug Reaction Following Granulocyte Colony-Stimulating Factor Administration in Nasopharynx Cancer Patient with Febrile Neutropenia: A Case Report - Randy Adiwinata; Andrea Livina; Harlinda Haroen; Linda Rotty; Paul N Harijanto; Agung Nugroho; Cecilia Hendratta; Pearla Lasut; Christian Kawengian (Indonesian Journal of Cancer, 2022)
Introduction: Several side effects may occur during cancer treatment such as myelosuppression following systemic chemotherapy, which is mainly manifested as neutropenia and is associated with increased infection risk. Febrile neutropenia is associated with a worse prognosis. Granulocyte colony-stimulating factor (G-CSF) may be given prophylactically before chemotherapy in selected cases or as adjuvant therapy in febrile neutropenia. G-CSF administration may be associated with several side effects, including skin manifestation. More rarely, G-CSF administration may induce acute febrile neutrophilic dermatosis is which known as a Sweet syndrome. Case Presentation: A 63-year-old man with nasopharyngeal cancer stage III on chemotherapy and radiotherapy came to our emergency department with a chief complaint of fever, coughing, and shortness of breath. He was diagnosed with community-acquired pneumonia and febrile neutropenia. His white blood cell (WBC) count was 200/mm3 . On the third day of hospitalization and G-CSF administration, he developed a rash and had skin desquamation mainly on his head including the scalp, face, lips, upper trunk, arms, and the surface of both hands. His follow-up laboratory result was WBC 8300/mm3 with a neutrophil count of 87%. Presumable Sweet syndrome diagnosis with differential diagnosis of other drug eruption reactions was made. Systemic and topical were administered, and G-CSF was stopped. Significant improvement was observed. Conclusions: G-CSF administration in febrile neutropenic cancer is generally safe; however, several adverse events may occur. Cutaneous adverse events following G-CSF administration should be recognized and treated accordingly. Sweet syndrome is rare but should be recognized as a possible G-CSF-induced drug skin complication.